Lipid metabolism marker CD36 is associated with 18FDG-PET/CT false negative lymph nodes in head and neck squamous cell carcinoma - Meng, Xiaoyan; Sun, Jingjing; Xu, Feng; Liu, Zhonglong; He, Yue (Frontiers in Oncology, 2023)
Background: Lymph node metastasis frequently occurs in head and neck squamous cell carcinoma (HNSCC) patients, and [18F] fluorodeoxyglucose positron emission tomography with computed tomography (18FDG-PET/CT) examination for lymph node metastasis could result in false negativity and delay following treatment. However, the mechanism and resolution for 18FDG-PET/CT false negatives remain unclear. Our study was aim to found biomarkers for false negativity and true positivity from a metabolic perspective. Methods: Ninety-two patients diagnosed with HNSCC who underwent preoperative 18FDG-PET/CT and subsequent surgery in our institution were reviewed. Immunohistochemistry (IHC) examinations of glucose metabolism (GLUT1 and GLUT5), amino acid metabolism (GLS and SLC1A5), and lipid metabolism (CPT1A and CD36) markers were conducted on their primary lesion and lymph node sections. Results: We identified specific metabolic patterns of the false-negative group. Significantly, CD36 IHC score of primary lesions was higher in false-negative group than true-positive group. Moreover, we validated pro-invasive biological effects of CD36 by bioinformatics analysis as well as experiments. Conclusion: IHC examination of CD36 expression, which is a lipid metabolism marker, in primary lesions could distinguish HNSCC patients’ lymph nodes false negatives in 18FDG-PET/CT.